Highly efficient polymer solar cells employing natural chlorophyllin as a cathode interfacial layer. Issue 2 (11th December 2017) - Guan, Qian; Peng, Ruixiang; Liu, Zhiyang; Song, Wei; Yang, Rongjuan; Hong, Ling; Lei, Tao; Fan, Xi; Wei, Qiang; Ge, Ziyi
Abstract : Natural chlorophyllin was applied as cathode interfacial layer for PSCs, which present improved PCE up to 10.55%. Abstract : Development of green and low-cost interfacial materials is an important issue to promote the commercialization of polymer solar cells (PSC). In this study, a derivative of natural chlorophyll, called chlorophyllin (CuCN), is applied as a cathode interfacial layer (CIL) to effectively improve the charge-carrier transportation and collection of both fullerene and non-fullerene based PSCs. As a result, the high power conversion efficiency of 8.35% and 10.55% is achieved for fullerene PTB7:PC71 BM-based devices and non-fullerene PBDB-T:IT-M-based devices, respectively. Notably, the natural chlorophyllin is a green food additive with low cost and solution-processability. This study demonstrates that the environment-friendly chlorophyllin is a promising CIL material to fabricate highly efficient solution-processed PSCs with a large area and low cost.